The Impact of Maintenance Dredging on Water Quality and Phytoplankton Standing Stock in Kwan Phayao Lake, Thailand - Pithakpol, Santiwat (Asian Health, Science and Technology Reports, 2007)
This study focuses on the role of the lake dredging, the effect of seasonal changes and distribution of total suspended solids, changes in light levels, lake water quality and phytoplankton biomass in Kwan Phayao between November 2004 and October 2005. A water quality monitoring program was carried out in Kwan Phayao Lake, an internationally recognized wetland in the upper north region of Thailand, to determine the impact of lake dredging. Water samples were collected monthly from November 2004 to October 2005 at 10 stations. Results indicated extraordinary high total suspended solid (TSS) concentrations at the upper end of the lake during March and April 2005 when the inflow channel was being dredged. These high concentrations of TSS limited photosynthetic active radiation (PAR) light penetrating into the lake at depths of 60 cm and 40 cm in March and April, respectively. During July to October there were high water inflows into the lake with moderate TSS. During these months surface water was also partly covered by floating macrophytes, especially water hyacinth, resulting in low phytoplankton standing stock. Mean phytoplankton standing stocks, expressed as chlorophyll a, were higher than 100 mg m-3 between March and May 2005 due to algal blooms. Among 10 stations where data were collected, the lowest chlorophyll a recordings were concurrently observed at the most turbid site. Dissolved oxygen (DO) concentrations near lake bottom of this sampling site were also usually lower than DO criteria for the survival of aquatic animals. No correlation between rainfall and TSS was found in this study. Results indicated that the dredging activity had a minor effect on surface water pH, DO, and water temperature. However, the impact on PAR, phytoplankton standing stock, and dissolved inorganic materials were locally prominent.